A Review On FSO By Using Different Modulation Techniques - Miglani, Rajan; Charak, Sachal; Kumar Arora, Sandeep; Masud, Mahedi (International Journal of Engineering and Technology, 2018)
Now a days as we are seeing that the free space optics is one of the emerging technology used for the replacement of the radio frequency wireless communication, due to their advantages over it like cost, speed, bandwidth, minimum error as well as efficient communication. The quality of services provided by the FSO is far better than the RF communication network. The free space optics is unlicensed band which make it less costly than the licensed band technology. As the atmospheric channel is used for transmission the effects of atmospheric condition effects the communication. In this paper we try to discuss all the modulation schemes which help to improve the performances of the optic system.Â